Enterprise Social Policy as a Means of Development of Social Work - Špiláčková, Marie (Verlag Barbara Budrich, 2020)
Since its professional beginnings, social work has been a major actor and instrument of social policy. This study is a reconstruction of the development of social work in enterprises implemented as part of enterprise social policy in the territory of Bohemia and Moravia between the years 1876-1989. Using a hermeneutical approach based on historical research, the author explores the transformation of societal institutions, communities and structures.; Seit ihren professionellen Anfängen ist die Soziale Arbeit wichtiger Akteur und Instrument der Sozialpolitik. Die vorliegende Studie ist eine Rekonstruktion der Entwicklung der Sozialen Arbeit in Unternehmen, die im Rahmen der betrieblichen Sozialpolitik auf dem Gebiet Böhmens und Mährens in den Jahren 1876-1989 implementiert wurde. Mit Hilfe eines hermeneutischen Ansatzes, der auf historischer Forschung basiert, untersucht die Autorin den Wandel gesellschaftlicher Institutionen, Gemeinschaften und Strukturen.